ASSMANN, J., CACCIARI, M., DUQUE, F., PONS, J. y VELA, A. (2020). La palabra que falta. El dios indecible de Moisés y Aarón, de Schönberg. Madrid: Ediciones CBA. - Pérez Santonja, Gonzalo (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: ASSMANN, J., CACCIARI, M., DUQUE, F., PONS, J. y VELA, A. (2020). La palabra que falta. El dios indecible de Moisés y Aarón, de Schönberg. Madrid: Ediciones CBA.